Creative heritage of A.K. Tolstoy in interpretation by F.E. Paktovsky - Cherkasov, Valeriy (2018)
This article presents a conceptual analysis of F.E. Paktovsky, dedicated to the creative heritage of AK. Tolstoy. The relevance of this study is determined by the importance of the figure of the literary critic for the history of Russian criticism of the 19th and 20th centuries, the importance of his views on the creativity of the authors of Russian classical literature of the second half of the 19th century, and also for the history of the National University of BelSU as a whole, since the critic was one of the directors of Belgorod teacher's institute. Turning to the works of A.K. Tolstoy, a literary critic considers them as the embodiment of aesthetic views on the nature of art, he focuses attention on socio-political motives that were relevant to contemporary Russian social life.